MANAJEMEN KELAS OLEH GURU DALAM PEMBELAJARAN BAHASA ARAB DI KELAS VI SD ISLAM KARAWANG - Muhammad Raihan Firdaus; Pepen Suhendra; Mulhendra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify the implementation of classroom management byteachers in Arabic language instruction for sixth-grade students at Sekolah DasarIslam Karawang and to explore the challenges faced in its application. Thebackground of this research is based on the reality that Arabic language learning atthe elementary school level still encounters various obstacles, particularly becauseArabic is not the students’ everyday language. This research employed a qualitativeapproach with a descriptive method, allowing the researcher to gain an in-depthunderstanding of the strategies applied by teachers in managing the classroom.Data were collected through direct classroom observation, in-depth interviews withteachers and students, and documentation analysis related to the learning process.The findings indicate that teachers employ different classroom managementstrategies tailored to the characteristics and activity levels of the students. For activestudents, teachers provide group activities, discussions, and educational games tochannel their energy and enhance participation. Meanwhile, for less active students,teachers use more structured learning approaches, such as individual guidance andclear assignments. The main challenges faced by teachers include the diversity ofstudent abilities, low motivation to learn, disruptive behaviors from highly activestudents, and difficulties in learning Arabic as a foreign language. To address thesechallenges, teachers adopt flexible and adaptive approaches, give special attentionto students in need, and utilize a variety of teaching methods and media. This studyconcludes that effective classroom management is crucial for the success of Arabiclanguage instruction and can significantly enhance student engagement andachievement.